When Juvenile Delinquency Became an International Post-War Concern The United Nations, the Council of Europe and the Place of Greece - Avdela, Efi (2018)
This book examines how the intensive discussions about the issue of juvenile delinquency in the new international organizations (United Nations, World Health Organization, Council of Europe), which emerged after the end of the Second World War, internationalized the anxieties generated in the fifties and sixties by its purported increase in Europe and beyond. Greece, a regular member-state, anxious to ensure international legitimacy in the aftermath of the Civil War, presented abroad an embellished picture of the measures undertaken at home for the prevention and containment of juvenile delinquency, sidestepping the strong moralism and the juridical formalism that dominated both official and unofficial approaches.